The practice of genomic medicine: A delineation of the process and its governing principles - Handra, Julia; Elbert, Adrienne; Gazzaz, Nour; Moller-Hansen, Ashley; Hyunh, Stephanie; Lee, Hyun Kyung; Boerkoel, Pierre; Alderman, Emily; Anderson, Erin; Clarke, Lorne; Hamilton, Sara; Hamman, Ronnalea; et al. (Frontiers in Medicine, 2023)
Genomic medicine, an emerging medical discipline, applies the principles of evolution, developmental biology, functional genomics, and structural genomics within clinical care. Enabling widespread adoption and integration of genomic medicine into clinical practice is key to achieving precision medicine. We delineate a biological framework defining diagnostic utility of genomic testing and map the process of genomic medicine to inform integration into clinical practice. This process leverages collaboration and collective cognition of patients, principal care providers, clinical genomic specialists, laboratory geneticists, and payers. We detail considerations for referral, triage, patient intake, phenotyping, testing eligibility, variant analysis and interpretation, counseling, and management within the utilitarian limitations of health care systems. To reduce barriers for clinician engagement in genomic medicine, we provide several decision-making frameworks and tools and describe the implementation of the proposed workflow in a prototyped electronic platform that facilitates genomic care. Finally, we discuss a vision for the future of genomic medicine and comment on areas for continued efforts.